Preparation method of anti-skid and anti-freezing water permeable brick

By acid treatment of coal gangue and combining the mixture of grafted bentonite with ungrafted bentonite, the problem of insufficient freezing resistance of permeable bricks is solved, and higher anti-slip anti-freezing and freezing properties and internal strength are achieved.

CN119462073AInactive Publication Date: 2025-02-18ZONGYANG COUNTY HENGSHENG NEW BUILDING MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411435254.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing permeable bricks have poor freezing resistance, especially under low temperature conditions, which can easily lead to internal structure damage and reduce mechanical properties.

Method used

The acid treatment is carried out by coal gangue and sulfuric acid solution. The grafted bentonite and the ungrafted bentonite are mixed in a certain proportion as binder. During the preparation process, ceramic granules, quartz sand and other materials are added, and molded by pressing and Sintered to obtain permeable bricks that are anti-slip and freezing.

Benefits of technology

It improves the anti-slip and freezing properties of permeable bricks, enhances the internal strength, better resists the pressure of solid ice, and extends the service life of permeable bricks.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of water permeable bricks, and discloses a preparation method of an anti-skid and anti-freezing water permeable brick, which comprises the following steps: (1) obtaining acid-treated coal gangue; (2) obtaining a grafting solution; (3) obtaining grafted bentonite; (4) obtaining a binder; (5) obtaining a water-permeable green brick; and (6) obtaining the finished water permeable brick. The water permeable brick prepared by the preparation method disclosed by the invention has excellent anti-skid and anti-freezing properties, in the preparation process of the water permeable brick prepared by the preparation method disclosed by the invention, the surface of the water permeable brick is pressed, smoother and then fired, so that a uniformly dispersed concave-convex structure is generated on the surface of the water permeable brick, and the concave-convex structure can greatly improve the friction force between a shoe sole and the water permeable brick; especially in rainy and snowy days, due to the fact that high friction resistance is provided, the remarkable anti-skid effect can be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of permeable bricks, in particular to a method for preparing anti-skid and anti-freezing permeable bricks. Background Art

[0002] In recent years, with the increase in rainy weather, urban drainage pressure has been greatly challenged. Urban flooding incidents have occurred frequently due to continuous heavy rain and rainstorms. Moreover, as the size of cities continues to expand, the pressure on urban drainage systems has also continued to increase.

[0003] At present, most permeable bricks are made of slag waste as raw materials. They are pressed into shape and finally sintered at high temperature to obtain finished permeable bricks. Permeable bricks have certain permeability and can transfer surface water to the underground in time, which can greatly reduce the pressure of urban drainage systems. They are widely used in public places such as sidewalks, city squares and parking lots.

[0004] However, the antifreeze performance of the permeable bricks prepared by the prior art is relatively poor, especially when used outdoors at low temperatures. Since the temperature is below 0°C, the water in the permeable bricks will condense into ice. After condensing into ice, the volume will expand, thereby squeezing the inside of the permeable bricks, easily causing the internal structure of the permeable bricks to be destroyed, thereby greatly reducing the mechanical properties of the permeable bricks.

[0005] Based on this, we proposed a method for preparing anti-slip and anti-freezing permeable bricks. Summary of the invention

[0006] 1. Technical issues to be resolved

[0007] In view of the deficiencies in the prior art, the present invention provides a method for preparing anti-skid and anti-freezing permeable bricks.

[0008] (II) Technical solution

[0009] To achieve the above-mentioned purpose, the present invention provides the following technical solutions:

[0010] A method for preparing anti-skid and anti-freezing permeable bricks comprises the following steps:

[0011] (1) adding coal gangue and sulfuric acid solution in a ratio of 15-20 g: 200 mL, stirring for 10 min at room temperature, raising the temperature to 90° C., stirring for 30 min, filtering, washing to neutrality, and drying to obtain acid-treated coal gangue;

[0012] (2) adding dodecyl dimethyl tertiary amine to water, stirring and mixing, then adding hydrochloric acid solution, adjusting the pH of the system to 3.5, then adding epichlorohydrin, adjusting the temperature to 75° C., keeping warm and stirring for 2 hours to obtain a grafting solution;

[0013] (3) adding bentonite to the grafting solution prepared in step (2), adjusting the temperature to 60° C., stirring for 2 hours, filtering, washing to neutrality, and drying to obtain grafted bentonite;

[0014] (4) stirring and mixing the grafted bentonite and the untreated bentonite in a mass ratio of 1:10-15 to obtain a binder;

[0015] (5) adding acid-treated coal gangue, binder, ceramsite, quartz sand and water into a mixer in sequence, stirring and mixing them evenly, then injecting them into a mold, pressing and molding them, and then drying them to obtain a permeable brick blank;

[0016] (6) The dried permeable brick blanks are fired in a firing kiln to obtain finished permeable bricks.

[0017] As a further technical solution, the mass fraction of the sulfuric acid solution in step (1) is 12.5%;

[0018] The drying step was performed at 60° C. for 1 hour.

[0019] As a further technical solution, in step (2), the mixing ratio of dodecyldimethyl tertiary amine and water is 3-5 g: 500 mL;

[0020] The concentration of the hydrochloric acid solution is 1.5 mol / L;

[0021] The molar ratio of epichlorohydrin to dodecyldimethyl tertiary amine is 1:1.

[0022] As a further technical solution: in step (3), the mixing ratio of bentonite and grafting liquid is 22-25 g: 180 mL;

[0023] Among them, the stirring speed of the heat preservation stirring is 1200r / min;

[0024] The drying temperature was 65°C and the drying time was 40 minutes.

[0025] As a further technical solution: the stirring speed of the stirring and mixing in step (4) is 800 r / min;

[0026] The stirring and mixing time is 30 minutes.

[0027] As a further technical solution, in step (5), the acid-treated coal gangue, binder, ceramsite, quartz sand and water are mixed in a mass ratio of 40-50:18-23:15-18:8-12:8-10.

[0028] As a further technical solution, the pressing pressure in step (5) is 10-12 MPa, and the pressing time is 40-50 s.

[0029] As a further technical solution: the drying in step (5) is: drying the permeable brick blanks until the water content is less than 5%.

[0030] As a further technical solution: in step (6), the sintering temperature is 1050-1080° C. and the sintering time is 2.5 hours.

[0031] (III) Beneficial effects

[0032] Compared with the prior art, the present invention provides a method for preparing anti-skid and anti-freezing permeable bricks, which has the following beneficial effects:

[0033] The permeable bricks prepared by the present invention have excellent anti-skid and anti-freezing properties. During the preparation process, the surface of the permeable bricks prepared by the present invention is pressed to be relatively flat, and then after firing, a dispersed concave-convex structure is generated on the surface of the permeable bricks. This concave-convex structure can greatly increase the friction between the sole and the permeable bricks, especially in rainy and snowy weather, because it provides a higher friction resistance, it can have a significant anti-skid effect.

[0034] The permeable bricks prepared by the present invention have a large number of pore structures inside, mainly because they have excellent liquid water transmission capabilities. In this way, surface rainwater can be transferred to the underground in time on rainy days, which can prevent the generation of large amounts of water accumulation in cities. At that time, when the weather is relatively cold, especially when the temperature is below the freezing point, the water in the permeable bricks will condense from liquid to ice, and after the water changes from liquid to solid ice, its volume will expand, which will produce a certain pressure on the inside of the permeable bricks. However, the present invention adopts a mixture of grafted bentonite and ungrafted bentonite in a certain proportion as a binder, which has a significant effect on improving the internal strength of the permeable bricks. In this way, it can better resist the pressure of solid ice on the internal structure of the permeable bricks and improve the antifreeze performance of the permeable bricks. DETAILED DESCRIPTION

[0035] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0036] Example 1

[0037] A method for preparing anti-skid and anti-freezing permeable bricks comprises the following steps:

[0038] (1) adding coal gangue and sulfuric acid solution in a ratio of 15 g: 200 mL, stirring for 10 min at room temperature, raising the temperature to 90° C., stirring for 30 min, filtering, washing to neutrality, and drying to obtain acid-treated coal gangue; the mass fraction of the sulfuric acid solution is 12.5%;

[0039] The drying step was performed at 60° C. for 1 hour.

[0040] (2) Add dodecyl dimethyl tertiary amine to water, stir and mix evenly, then add hydrochloric acid solution, adjust the pH of the system to 3.5, then add epichlorohydrin, adjust the temperature to 75°C, keep warm and stir for 2 hours to obtain a grafting solution; the mixing ratio of dodecyl dimethyl tertiary amine and water is 3g:500mL;

[0041] The concentration of the hydrochloric acid solution is 1.5 mol / L;

[0042] The molar ratio of epichlorohydrin to dodecyldimethyl tertiary amine is 1:1.

[0043] (3) Adding bentonite to the grafting solution prepared in step (2), adjusting the temperature to 60° C., stirring for 2 hours, filtering, washing to neutrality, and drying to obtain grafted bentonite; the mixing ratio of bentonite to grafting solution is 22 g:180 mL;

[0044] Among them, the stirring speed of the heat preservation stirring is 1200r / min;

[0045] The drying temperature was 65°C and the drying time was 40 minutes.

[0046] (4) stirring and mixing the grafted bentonite and the untreated bentonite in a mass ratio of 1:10 to obtain a binder; the stirring speed of the stirring and mixing is 800 r / min;

[0047] The stirring and mixing time is 30 minutes.

[0048] (5) Add acid-treated coal gangue, binder, expanded clay, quartz sand and water to a mixer in sequence, stir and mix them evenly, then inject them into a mold, press and form them, and then dry them to obtain permeable bricks; the mass ratio of acid-treated coal gangue, binder, expanded clay, quartz sand and water is 40:18:15:8:8; the pressing pressure is 10 MPa, and the pressing time is 40 s; drying is to dry the permeable bricks until the water content is less than 5%.

[0049] (6) The dried permeable brick blanks are fired in a firing kiln to obtain finished permeable bricks; the sintering temperature is 1050° C. and the time is 2.5 hours.

[0050] Example 2

[0051] A method for preparing anti-skid and anti-freezing permeable bricks comprises the following steps:

[0052] (1) adding coal gangue and sulfuric acid solution in a ratio of 16 g: 200 mL, stirring for 10 min at room temperature, raising the temperature to 90° C., stirring for 30 min, filtering, washing to neutrality, and drying to obtain acid-treated coal gangue; the mass fraction of the sulfuric acid solution is 12.5%;

[0053] The drying step was performed at 60° C. for 1 hour.

[0054] (2) Add dodecyl dimethyl tertiary amine to water, stir and mix evenly, then add hydrochloric acid solution, adjust the pH of the system to 3.5, then add epichlorohydrin, adjust the temperature to 75°C, keep warm and stir for 2 hours to obtain a grafting solution; the mixing ratio of dodecyl dimethyl tertiary amine and water is 3.5g:500mL;

[0055] The concentration of the hydrochloric acid solution is 1.5 mol / L;

[0056] The molar ratio of epichlorohydrin to dodecyldimethyl tertiary amine is 1:1.

[0057] (3) Adding bentonite to the grafting solution prepared in step (2), adjusting the temperature to 60° C., stirring for 2 hours, filtering, washing to neutrality, and drying to obtain grafted bentonite; the mixing ratio of bentonite to grafting solution is 23 g:180 mL;

[0058] Among them, the stirring speed of the heat preservation stirring is 1200r / min;

[0059] The drying temperature was 65°C and the drying time was 40 minutes.

[0060] (4) stirring and mixing the grafted bentonite and the untreated bentonite in a mass ratio of 1:14 to obtain a binder; the stirring speed of the stirring and mixing is 800 r / min;

[0061] The stirring and mixing time is 30 minutes.

[0062] (5) Add acid-treated coal gangue, binder, expanded clay, quartz sand and water to a mixer in sequence, stir and mix them evenly, then inject them into a mold, press and form them, and then dry them to obtain permeable bricks; the mass ratio of acid-treated coal gangue, binder, expanded clay, quartz sand and water is 42:21:16:9:9.6; the pressing pressure is 10.5 MPa, and the pressing time is 46 s; drying is to dry the permeable bricks until the water content is less than 5%.

[0063] (6) The dried permeable brick blanks are fired in a firing kiln to obtain finished permeable bricks; the sintering temperature is 1075°C and the time is 2.5 hours.

[0064] Example 3

[0065] A method for preparing anti-skid and anti-freezing permeable bricks comprises the following steps:

[0066] (1) adding coal gangue and sulfuric acid solution in a ratio of 18 g: 200 mL, stirring for 10 min at room temperature, raising the temperature to 90° C., stirring for 30 min, filtering, washing to neutrality, and drying to obtain acid-treated coal gangue; the mass fraction of the sulfuric acid solution is 12.5%;

[0067] The drying step was performed at 60° C. for 1 hour.

[0068] (2) Add dodecyl dimethyl tertiary amine to water, stir and mix evenly, then add hydrochloric acid solution, adjust the pH of the system to 3.5, then add epichlorohydrin, adjust the temperature to 75°C, keep warm and stir for 2 hours to obtain a grafting solution; the mixing ratio of dodecyl dimethyl tertiary amine and water is 4g:500mL;

[0069] The concentration of the hydrochloric acid solution is 1.5 mol / L;

[0070] The molar ratio of epichlorohydrin to dodecyldimethyl tertiary amine is 1:1.

[0071] (3) Adding bentonite to the grafting solution prepared in step (2), adjusting the temperature to 60° C., stirring for 2 hours, filtering, washing to neutrality, and drying to obtain grafted bentonite; the mixing ratio of bentonite to grafting solution is 23 g:180 mL;

[0072] Among them, the stirring speed of the heat preservation stirring is 1200r / min;

[0073] The drying temperature was 65°C and the drying time was 40 minutes.

[0074] (4) stirring and mixing the grafted bentonite and the untreated bentonite in a mass ratio of 1:12 to obtain a binder; the stirring speed of the stirring and mixing is 800 r / min;

[0075] The stirring and mixing time is 30 minutes.

[0076] (5) Add acid-treated coal gangue, binder, expanded clay, quartz sand and water to a mixer in sequence, stir and mix them evenly, then inject them into a mold, press and form them, and then dry them to obtain permeable bricks; the mass ratio of acid-treated coal gangue, binder, expanded clay, quartz sand and water is 45:21:16:10:9; the pressing pressure is 11 MPa, and the pressing time is 46 s; drying is to dry the permeable bricks until the water content is less than 5%.

[0077] (6) The dried permeable brick blanks are fired in a firing kiln to obtain finished permeable bricks; the sintering temperature is 1060° C. and the time is 2.5 hours.

[0078] Example 4

[0079] A method for preparing anti-skid and anti-freezing permeable bricks comprises the following steps:

[0080] (1) adding coal gangue and sulfuric acid solution in a ratio of 20 g: 200 mL, stirring for 10 min at room temperature, raising the temperature to 90° C., stirring for 30 min, filtering, washing to neutrality, and drying to obtain acid-treated coal gangue; the mass fraction of the sulfuric acid solution is 12.5%;

[0081] The drying step was performed at 60° C. for 1 hour.

[0082] (2) Add dodecyl dimethyl tertiary amine to water, stir and mix evenly, then add hydrochloric acid solution, adjust the pH of the system to 3.5, then add epichlorohydrin, adjust the temperature to 75°C, keep warm and stir for 2 hours to obtain a grafting solution; the mixing ratio of dodecyl dimethyl tertiary amine and water is 5g:500mL;

[0083] The concentration of the hydrochloric acid solution is 1.5 mol / L;

[0084] The molar ratio of epichlorohydrin to dodecyldimethyl tertiary amine is 1:1.

[0085] (3) Adding bentonite to the grafting solution prepared in step (2), adjusting the temperature to 60° C., stirring for 2 hours, filtering, washing to neutrality, and drying to obtain grafted bentonite; the mixing ratio of bentonite to grafting solution is 25 g:180 mL;

[0086] Among them, the stirring speed of the heat preservation stirring is 1200r / min;

[0087] The drying temperature was 65°C and the drying time was 40 minutes.

[0088] (4) stirring and mixing the grafted bentonite and the untreated bentonite in a mass ratio of 1:15 to obtain a binder; the stirring speed of the stirring and mixing is 800 r / min;

[0089] The stirring and mixing time is 30 minutes.

[0090] (5) Add acid-treated coal gangue, binder, expanded clay, quartz sand and water to a mixer in sequence, stir and mix them evenly, then inject them into a mold, press and form them, and then dry them to obtain permeable bricks; the mass ratio of acid-treated coal gangue, binder, expanded clay, quartz sand and water is 50:23:18:12:10; the pressing pressure is 12 MPa, and the pressing time is 50 s; drying is to dry the permeable bricks until the water content is less than 5%.

[0091] (6) The dried permeable brick blanks are fired in a firing kiln to obtain finished permeable bricks; the sintering temperature is 1080° C. and the time is 2.5 hours.

[0092] Comparative Example 1

[0093] Based on Example 1, all the binders were replaced with untreated bentonite.

[0094] test

[0095] The embodiment and the comparative example were made into bricks of 240 mm × 115 mm × 53 mm (the actual deviation was ± 3 mm);

[0096] GB / T 2542-2012 "Test methods for wall bricks" was used for compressive strength testing;

[0097] Table 1

[0098] Compressive strength MPa Example 1 62.1 Example 2 63.3 Example 3 62.5 Example 4 62.8 Comparative Example 1 41.1

[0099] It can be seen from Table 1 that the permeable bricks prepared by the present invention have higher compressive strength.

[0100] The water permeability coefficient of the water-permeable bricks of the example samples was tested with reference to GB / T 25993-2010:

[0101] Table 2

[0102] Water permeability cm / s Example 1 0.12 Example 2 0.15 Example 3 0.16 Example 4 0.13

[0103] It can be seen from Table 2 that the permeable bricks prepared by the present invention have excellent water permeability.

[0104] Freeze-thaw cycle test:

[0105] The brick samples of the embodiment and the comparative example were placed in a freeze-thaw cycle tester at -15℃ to 20℃, with a distance of 50mm between any two bricks. The bricks were cooled to -15℃, kept warm for 1 hour, and then heated to 20℃ and kept warm for 30min as one freeze-thaw cycle. A total of 50 cycles were performed, and then the compressive strength test was performed. The compressive strength loss rate of the bricks before and after the test was compared:

[0106] Table 3

[0107] Compressive strength loss rate % Example 1 6.37 Example 2 6.83 Example 3 6.55 Example 4 6.42 Comparative Example 1 15.69

[0108] It can be seen from Table 3 that the permeable bricks prepared by the present invention have high antifreeze performance. Although the embodiments of the present invention have been shown and described, it is understood by those skilled in the art that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of the present invention, and the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing anti-skid and anti-freezing permeable bricks, characterized in that: The following steps are involved: (1) adding coal gangue and sulfuric acid solution in a ratio of 15-20 g: 200 mL, stirring for 10 min at room temperature, raising the temperature to 90° C., stirring for 30 min, filtering, washing to neutrality, and drying to obtain acid-treated coal gangue; (2) adding dodecyl dimethyl tertiary amine to water, stirring and mixing, then adding hydrochloric acid solution, adjusting the pH of the system to 3.5, then adding epichlorohydrin, adjusting the temperature to 75° C., keeping warm and stirring for 2 hours to obtain a grafting solution; (3) adding bentonite to the grafting solution prepared in step (2), adjusting the temperature to 60° C., stirring for 2 hours, filtering, washing to neutrality, and drying to obtain grafted bentonite; (4) stirring and mixing the grafted bentonite and the untreated bentonite in a mass ratio of 1:10-15 to obtain a binder; (5) adding acid-treated coal gangue, binder, ceramsite, quartz sand and water into a mixer in sequence, stirring and mixing them evenly, then injecting them into a mold, pressing and molding them, and then drying them to obtain a permeable brick blank; (6) The dried permeable brick blanks are fired in a firing kiln to obtain finished permeable bricks.

2. The method for preparing a non-slip and anti-freezing permeable brick according to claim 1, characterized in that: The mass fraction of sulfuric acid solution in step (1) is 12.5%; The drying step was performed at 60° C. for 1 hour.

3. The method for preparing a non-slip and anti-freezing permeable brick according to claim 1, characterized in that: In step (2), the mixing ratio of dodecyldimethyl tertiary amine and water is 3-5 g: 500 mL; The concentration of the hydrochloric acid solution is 1.5 mol / L; The molar ratio of epichlorohydrin to dodecyldimethyl tertiary amine is 1:

1.

4. The method for preparing a non-slip and anti-freezing permeable brick according to claim 2, characterized in that: In step (3), the mixing ratio of bentonite and grafting liquid is 22-25 g: 180 mL; Among them, the stirring speed of the heat preservation stirring is 1200r / min; The drying temperature was 65°C and the drying time was 40 minutes.

5. The method for preparing a non-slip and anti-freezing permeable brick according to claim 1, characterized in that: The stirring speed of the stirring and mixing in step (4) is 800 r / min; The stirring and mixing time is 30 minutes.

6. The method for preparing a non-slip and anti-freezing permeable brick according to claim 1, characterized in that: In step (5), the acid-treated coal gangue, binder, ceramsite, quartz sand and water are mixed in a mass ratio of 40-50:18-23:15-18:8-12:8-10.

7. The method for preparing a non-slip and anti-freezing permeable brick according to claim 1, characterized in that: The pressing pressure in step (5) is 10-12 MPa, and the pressing time is 40-50 s.

8. The method for preparing a non-slip and anti-freezing permeable brick according to claim 1, characterized in that: The drying in step (5) is as follows: drying the permeable brick blanks until the water content is less than 5%.

9. The method for preparing a non-slip and anti-freezing permeable brick according to claim 1, characterized in that: In step (6), the sintering temperature is 1050-1080° C. and the sintering time is 2.5 hours.